2010
DOI: 10.1021/jp910766q
|View full text |Cite
|
Sign up to set email alerts
|

Quest for Mode of Binding of 2-(4-(Dimethylamino)styryl)-1-methylpyridinium Iodide with Calf Thymus DNA

Abstract: The mode of binding of 2-(4-(dimethylamino)styryl)-1-methylpyridinium iodide (DASPMI) with calf thymus DNA as revealed from different steady state and time-resolved emission spectroscopic measurements has been reported in this paper. Fluorescence enhancement of DASPMI and its quenching by potassium iodide (KI) points to groove binding of dye with ct-DNA, rather than intercalation in the ct-DNA helix. An increase in steady state anisotropy and fluorescence lifetime hints at binding with ct-DNA. The value of bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
142
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(158 citation statements)
references
References 49 publications
12
142
0
Order By: Relevance
“…It is reported that, in case of minor groove binding and electrostatic binding, the CD spectra show insignificant change whereas, intercalating binding causes a remarkable change in the positive and negative bands [37]. As illustrated in Figure 5, after addition of PSDF to the DNA solution does not produced any significant change in the intrinsic CD spectrum of the DNA indicating that binding of PSDF with CTDNA does not disturb the stacking of bases.…”
Section: Circular Dichroism Spectroscopymentioning
confidence: 88%
“…It is reported that, in case of minor groove binding and electrostatic binding, the CD spectra show insignificant change whereas, intercalating binding causes a remarkable change in the positive and negative bands [37]. As illustrated in Figure 5, after addition of PSDF to the DNA solution does not produced any significant change in the intrinsic CD spectrum of the DNA indicating that binding of PSDF with CTDNA does not disturb the stacking of bases.…”
Section: Circular Dichroism Spectroscopymentioning
confidence: 88%
“…Molecular modeling studies can gain some important insight into the binding interactions between ligands and DNA [50].…”
Section: Molecular Modelingmentioning
confidence: 99%
“…The interaction of small molecules with DNA is gaining interest in the area of medicinal chemistry for exploring the structural and functional features of macromolecules to design new and effective drugs against various diseases [1]. Synthetic indol alkaloids such as β-carboline alkaloid possessing large pharmaceutical activities, particularly as a potential antitumoral agent by way of intercalation into DNA and inhibition of topoisomerase I and II [2].…”
Section: Introductionmentioning
confidence: 99%